Influence of sympathetic vasoconstrictor tone on conduit artery retrograde and oscillatory shear: Effects of habitual aerobic exercise in middle-aged and older adults - Koichiro Tanahashi; Jun Sugawara; Yuriko Sawano; Seiji Maeda (Japanese Society of Physical Fitness and Sports Medicine, 2018)
Retrograde and oscillatory shear can induce profound pro-atherogenic effects on endothelial cells, and increase with advancing age in peripheral conduit arteries. Habitual aerobic exercise ameliorates conduit artery retrograde and oscillatory shear in middle-aged and older adults; however, the mechanisms underlying the change in conduit artery shear rate patterns caused by habitual aerobic exercise remains unclear. This study investigated the role of sympathetic vasoconstrictor tone in the habitual aerobic exercise-induced change in conduit artery shear in middle-aged and older adults. Fifteen healthy middle-aged and older adults (aged 52-67 years; 4 men, 11 women) were divided into physically-active and sedentary control groups, based on reported exercise history. We measured brachial artery shear rate patterns at rest and during sympathetic nerve activity stimulation (via lower body negative pressure [LBNP] at -20 mmHg). At rest, the physically-active group showed smaller brachial artery retrograde and oscillatory shear compared to a sedentary control group (p < 0.05). The levels of brachial retrograde and oscillatory shear were elevated by the LBNP stimulation in the physically active group (p < 0.05), but not in the sedentary control group. Our results suggest that the attenuated basal sympathetic vasoconstrictor tone may contribute to the habitual aerobic exercise-induced decreases in conduit artery retrograde and oscillatory shear at rest in middle-aged and older adults.